EVALUATION OF APPLICATION OF INTERNATIONAL PROSTATE SYMPTOMS SCORE IN SUDANESE PATIENTS WITH BENIGN PROSTATIC HYPERPLASIA - M. Elbadawi, Omran; Khalid, Khalid Eltahir; M. Ahmed, Mohammed El Imam (Gezira Journal of Health Sciences; Vol 6 No 2 (2010), 2010)
Objectives: The purpose of the present study is to assess the reliability and validity of IPSS in pre- and treatment of Sudanese patients with BPH. Material and methods: In a descriptive prospective study, 350 Sudanese patients with LUTS attended the Urology department of Gezira Hospital for Renal Diseases and Surgery from September 2003 to April 2006. They were interviewed by urologists and answered the International Prostate Symptom Score (IPSS) questionnaire. Clinical work up was done for all only patients with benign hyperplasia were included in the analysis .Europeans guideline was adopted in the management and the out come was also subjected to IPSS evaluation. Results: The most common voiding symptoms was a weak stream (93% of subjects), followed by intermittency (57%) and hesitancy (54%). The most prevalence of storage symptoms was nocturia (87% of subjects), followed by frequency (73%) and urgency (64%). 64% of the study subjects   presented with severe IPSS, 33% with moderate IPSS, while only 3% of the patients presented with mild IPSS. Digital rectal examination (DRE) was done to all study subjects. There was no significant correlation between DRE and IPSS reported. The postoperative IPSS post treatment follow up was mild in 87%, moderate in 4% and sever in 9% of the patients.   Conclusion: Our study indicates that IPSS is informative and reproducible in assessment of patients with BPH.